1975
DOI: 10.1111/j.1748-5827.1975.tb05740.x
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence and microbiology of otitis externa in the dog

Abstract: The occurrence of otitis externa in dogs in relation to ear types, age‐group, sex, months and seasons of the year and microbiology of canine ears was studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
29
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 7 publications
5
29
0
Order By: Relevance
“…In this study, only German shepherds had significantly higher EECH than other breeds in non-OE groups. These findings may suggest that relative humidity in the ear canals unlikely predisposes specific breeds to OE, and ear type (pendulous or erect) does not affect the retention of heat and moisture in the ear canal as much as previously reported [6,7,14].…”
supporting
confidence: 53%
See 1 more Smart Citation
“…In this study, only German shepherds had significantly higher EECH than other breeds in non-OE groups. These findings may suggest that relative humidity in the ear canals unlikely predisposes specific breeds to OE, and ear type (pendulous or erect) does not affect the retention of heat and moisture in the ear canal as much as previously reported [6,7,14].…”
supporting
confidence: 53%
“…Ear type has been reported to predispose the animal to OE by altering the microclimate [6,7,14]. Although it seems plausible that pendulous and hirsute ear may result in increased EECT, Huang and Huang [8] concluded that EECT may play a lesser role in the development of OE in dogs.…”
mentioning
confidence: 99%
“…Concerning the Pseudomonas strains (prevalence: 18.10%; Sharma and Rhodes, 1975), the extract showed MIC at 150 µg/ml (P. cepacia) and 250 µg/ml (P. aeruginosa), and MBC at 250 µg/ml and 500 µg/ml.…”
Section: Resultsmentioning
confidence: 95%
“…was the most commonly isolated microorganism together with M. pachydermatis from animals with OE (26 cases) and from healthy ones (11 cases). This fact is probably related to the ability of the microorganisms to utilize metabolic products of each other and can synergically cause chronic otitis (Sharma andRoades, 1975, Kiss et al, 1997) Complete inhibitory effect was obtained, in vitro, against M. pachydermatis, with four imidazole compounds (ketoconazole, econazole, miconazole, clotrimazole), whereas nystatin was effective only in 38 isolates and not effective in the remaining 8. These results are consistent with the findings of earlier studies (Dufait, 1981, Kures et al, 1983, Uchida et al, 1990b.…”
Section: Discussionmentioning
confidence: 99%
“…The microbial flora of the normal ear canal is constituted primary of Staphylococci, non-haemolytic Streptococci and the yeast M pachydermatis (Grono and Frost 1969, Sharma and Roades 1975, Cole et al, 1998. Coagulase positive S .intermedins strains and M. pachydermatis are the most common isolates in cases of canine otitis externa (OE).…”
Section: Introductionmentioning
confidence: 99%